Europeans flock to Paris Pan Festival - Joseph, Terry (Express)
Bands from Britain, France, Finland, Switzerland and Germany competed in a preliminary round in May 2000 to get to World Steelband Music Festival in Trinidad in October 2000. Judges were Dr. Anne Osborne, Dr. Richard Murphy and Dr. Eugene Novotney.
Keywords: Music festivals -- Europe; Steel bands (Music) -- Europe; World Steelband Music Festival